Factors affecting sequential sex allocation in the parasitoid wasp Gryon japonicum. Issue 2 (13th January 2018) - Todoroki, Yusuke; Numata, Hideharu
Abstract: Female wasps of the solitary egg parasitoid Gryon japonicum (Hymenoptera: Platygastridae) allocate male and female offspring in a particular sequence to successive hosts. Male eggs are typically laid in the second host, and the sex allocation sequence is reset after a certain period of time. The present study aimed to examine the underlying mechanism to hold information and reset the sequence by using eggs of Riptortus pedestris (Heteroptera: Alydidae) as hosts. After completion of initial oviposition, a female wasp was treated by cold anesthesia for 1 h, exposure to a parasitized host for 3 h, or being kept at 15°C in darkness for 24 h, and then presented with three host eggs. Cold‐anesthetized females did not reset the sex allocation sequence, indicating that cold anesthesia did not block the mechanism of holding information about oviposition order. Frequent encounters with parasitized hosts were also insufficient to reset the sequence. However, being kept in cool, dark conditions significantly affected resetting, suggesting that low temperature lengthened the time required to reset the sequence. This implies that it is probable that the mechanism to hold information and reset sex allocation sequence in G. japonicum involves metabolism. Abstract : Female wasps lay male eggs typically in the second host, and the sex allocation sequence is reset after a certain period of time. Cold‐anesthesia did not block the mechanism of holding information about oviposition order, and frequent encounter with a parasitized host was also insufficient to reset the sequence. However, being kept in cool, dark conditions significantly affected resetting, suggesting that the mechanism of resetting sex allocation sequence involves metabolism.